Penerapan Teknologi Sistem Informasi untuk Mendukung Informasi dan Promosi pada Kaliwungu Printing - Edy Siswanto; Arie Atwa Magriyanti; Achmad Bachtiari (Teknik: Jurnal Ilmu Teknik dan Informatika, 2025)
This study is motivated by the declining revenue of Kaliwungu Printing every month, which is caused by the inconsistency in product promotion. As a result, the lack of regular and comprehensive promotional efforts has led to limited public awareness of Kaliwungu Printing. The purpose of this research is to develop a structured and comprehensive promotional tool to showcase the products offered by Kaliwungu Printing. This research employs a qualitative method to obtain accurate and relevant data. Data collection techniques include observation, interviews, and questionnaires. The respondents consist of media experts, content experts, and a group of five employees from Kaliwungu Printing. The validity of the data is measured using the rating scale method proposed by Sugiyono. The results of the study show a score of 30 from media experts, 36 from content experts, and an 84% validity rate from the group assessment. Based on the overall evaluation indicators, these results fall into the "very good" category. Thus, the study concludes that the proposed promotional tool is suitable for implementation and can be utilized effectively